Innovation of Islamic Religious Learning Based on Multiculturalism - Bukhari, Bukhari, (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: this research was done conceptually, namely researchers collect research data from existing literacy, then conducted a narrative-descriptive study related to Islamic religious learning in madrassas. Researchers mapped the multicultural aspects and values applied in learning. The results showed that PAI learning based multicultural at the Madrasah Aliyah level should be seen aspects of the development of learners, aged 14-18 years. At this stage the subjects must reflect multicultural values, namely students are able to maintain mutual understanding, and show mutual respect. At this level students are already able to get to know themselves by discussing with others, who are culturally different. This aims so that students can distinguish multicultural aspects around them and be able to live in participation and cooperation. Efforts to instill multicultural attitudes for madrasah aliyah students can be done with three approaches, namely contributive, additive, and social action.